2011
DOI: 10.5402/2011/780150
|View full text |Cite
|
Sign up to set email alerts
|

Development and Evaluation of Microemulsions for Transdermal Delivery of Insulin

Abstract: Insulin-loaded microemulsions for transdermal delivery were developed using isopropyl myristate or oleic acid as the oil phase, Tween 80 as the surfactant, and isopropyl alcohol as the cosurfactant. The pseudoternary phase diagrams were constructed to determine the composition of microemulsions. The insulin permeation flux of microemulsions containing oleic acid as oil phase through excised mouse skin and goat skin was comparatively greater than that of microemulsions containing isopropyl myristate as oil phas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
38
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(39 citation statements)
references
References 27 publications
0
38
0
1
Order By: Relevance
“…A magnetic stirrer bar was fitted inside the receptor chamber, which was filled with phosphate buffer saline (PBS, pH 7.4) as receptor phase medium. A small concentration of sodium azide (0.0025 % w/v) was put into the system to prevent the occurrence of microbial growth [30][31]. The whole system was positioned over a magnetic stirrer at 37±0.7 °C.…”
Section: Ex Vivo Skin Permeation Experiments Of 4 % Lidocaine Hcl Gelsmentioning
confidence: 99%
“…A magnetic stirrer bar was fitted inside the receptor chamber, which was filled with phosphate buffer saline (PBS, pH 7.4) as receptor phase medium. A small concentration of sodium azide (0.0025 % w/v) was put into the system to prevent the occurrence of microbial growth [30][31]. The whole system was positioned over a magnetic stirrer at 37±0.7 °C.…”
Section: Ex Vivo Skin Permeation Experiments Of 4 % Lidocaine Hcl Gelsmentioning
confidence: 99%
“…In addition, several previous studies showed the benefits of MEs vehicle as an enhancer in dermal delivery. [20][21][22][23] The content of S/C mixture in ME samples affected the skin permeation rate of HQ significantly. As the content of S + C mixture was decreased from 85% to 35% at S/C = 3 (Km = 3), the skin permeation rate of HQ increased by 4-fold (ME-HQ-2).…”
Section: Characterization Of Hq Mesmentioning
confidence: 99%
“…The later possibility has high probability taking into consideration the nature of the main components of the tested microemulsion systems. For example oleic acid was shown to exert skin penetration enhancing effect for both hydrophilic and hydrophobic dugs from microemulsions (El Maghraby, 2012a;Malakar et al, 2011).…”
Section: Figmentioning
confidence: 99%